An adaptive microwave photonic filter with LMS algorithm. Issue 8 (24th May 2022) - Ding, Yujiao; Wang, Yue; Yang, Yuchen; Du, Cong; Dong, Wei
Abstract : A microwave photonic filter (MPF) with an adaptive algorithm is proposed and theoretically analyzed. The structure combines the finite impulse response (FIR) MPF with the adaptive algorithm. The FIR MPF includes variable optical attenuators (VOAs) and variable optical delay lines (VDLs). The least mean square (LMS) algorithm can calculate the weight coefficient of each tap in FIR MPF, which can influence the VOA to realize the adaptive filtering process. This adaptive MPF can extract the desired signal from noise precisely. The noise signal can be well suppressed and the signal-to-noise ratio (SNR) can be developed from 4.15 to 25.5 dB. In addition, this adaptive MPF can be suitable for a wide range of signals.